Entrepreneurship-Based Islamic Boarding School Development (A Study Of Tuan Guru Hasanain Juaini's Thoughts On Education) - Putra , Fibrian Khotmul Aula; Saparudin, Saparudin; Habiburrahman, Muhammad (AL-WIJDÃN Journal of Islamic Education Studies, 2024)
The entrepreneurship-based Islamic boarding school at Nurul Haramain began with the arrival of Tuan Guru Juaini Mukhtar to the Narmada area and the teachers' anxiety about the needs of their students. These two things have continued to develop since their inception until now and are even imitated by many Islamic boarding schools. This research aims to describe Tuan Guru Hasanain Juaini's thoughts, especially on entrepreneurship-based Islamic boarding school development. The method used is descriptive qualitative. Data collection techniques used interviews, observation, and documentation which were carried out for 2 months starting from May-June 2023. The research results revealed that the concept of entrepreneurship according to Tuan Guru Hasanain Juaini is a mandatory knowledge a person must have. Tuan Guru Hasanain's thoughts in developing Nurul Islamic Boarding School Haramain are based on entrepreneurship and trading by Islamic law which prioritizes hard work, honesty, discipline, open-mindedness, and simple living. Meanwhile, the implementation of Tuan Guru Hasanain's entrepreneurial thinking can be seen in the birth of businesses and business units at Nurul Pesantren Haramain including a mini bank, laundry, Haramain restaurant, bakery, Haramain Mart, livestock, sports, heavy equipment rental and others. As for the contribution of Tuan Guru Hasanain's thoughts in developing Nurul Pesantren Haramain, it could be said that the majority of those in the Islamic boarding school are the contribution of Tuan Guru Hasanain's thoughts from the smallest to the largest. Starting from losing small amounts of student money, and teachers' vehicle loans to building networks with the government, investors, and entrepreneurs. This thesis also concludes that in developing an entrepreneurship-based Islamic boarding school, it must start from a movement, whether it is successful or not, the most important thing is to start it first. When applied, Islamic Sharia in business can be a solution when there is a deadlock in various situations and conditions.   Keywords: Entrepreneurship, Thoughts of Tuan Guru Hasanain, Islamic Boarding School.